Pengaruh Corporate Social Responbility, Ukuran Perusahaan, dan Kualitas Audit terhadap Manajemen Laba - Anastasia Agatha; Sri Ayem (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The purpose of this study is to examine the effect of corporate social responsibility, company size, and audit quality on earnings management in LQ45 indexed companies in 2016-2019. The study used quantitative methods, the sample used was purposive sampling, there were 20 samples of which there were 80 observational data. The study used multiple linear regression analysis with the help of the IBM SPSS 20.0 program. the results of the study prove three important findings: (1) CSR has a positive effect on earnings management, (2) firm size has a positive effect on earnings management, and (3) audit quality has no significant effect on earnings management. Keywords: Earning Management, Corporate Social Responsibility, Company Size, Audit Quality